The Chinese version of the Health Professional Communication Skills Scale: Psychometric evaluation - Zhong, Xiaoying; Tang, Fangmei; Lai, Dongmei; Guo, Xiujing; Yang, Xiaorong; Hu, Rong; Li, Dehua; Lu, Yongguang; Liu, Sixu; Leal-Costa, César (Frontiers in Psychology, 2023)
Objective: This study aims to translate the Health Professional Communication Skills Scale (HP-CSS) into Chinese and assess its psychometric properties. Methods: A total of 836 health professional were recruited. The demographic characteristics form and HP-CSS were used for data collection. The psychometric properties of HP-CSS were evaluated by examining item analysis, construct validity, Known-groups discriminant validity, internal consistency and split-half reliability. Results: In terms of items analysis, the critical ratio (CR) of 18 items was both greater than 3 (CR ranging from 9.937 to 28.816), and the score of each item were positively correlated with the total score (r ranging from 0.357 to 0.778, P<0.001). The fit indices showed that the original correlated four factor model of HP-CSS was adequate: χ2 =722.801; df =126; χ2/df=5.737; RMSEA=0.075; CFI=0.923; NNFI=0.908; TLI=0.906; IFI=0.923. In terms of known-groups discriminant validity, the HP-CSS total score was related to gender, occupation, work years, and communication skill training. The Cronbach's α coefficient was 0.922 and the split-half reliability was 0.865 for the total scale. Conclusion: The Chinese version of HP-CSS is a reliable and valid instrument to evaluate the communication skill among health professional in China.